ANALISIS PREDIKSI KEBANGKRUTAN PADA PERUSAHAAN TEKSTIL DAN GARMEN PT SRI REJEKI ISMAN TBK PERIODE 2019–2024 - Novi, Novi Wijayanti; Asep Muhammad Lutfi (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to analyze the bankruptcy potential of the textile and garment company PT Sri Rejeki Isman Tbk for the 2019–2024 period using the Modified Altman Z”-Score model. The research employs a descriptive method with a quantitative approach, in which the analyzed data consist of financial statements processed through financial ratio calculations. The data were obtained secondarily from the company’s annual financial reports published on the official website www.sritex.co.id. The Modified Altman Z”-Score model includes four main ratios: Working Capital to Total Assets (X₁), Retained Earnings to Total Assets (X₂), Earnings Before Interest and Taxes to Total Assets (X₃), and Book Value of Equity to Total Liabilities (X₄). The results show that the Modified Z”-Score value of PT Sri Rejeki Isman Tbk experienced a significant decline during the 2019–2024 period. In 2019 and 2020, the company still demonstrated good financial performance with Z”-Score values of 5,26 and 4.75, respectively, which fall under the safe category. However, starting in 2021, the Z”-Score dropped sharply to –12,91 and remained negative through 2024, with an average value of –3,87, indicating a bankrupt condition. This reflects a deteriorating financial position due to liquidity pressure, increased debt burden, and the adverse impact of the COVID-19 pandemic on exports and global market demand. This study confirms that the Modified Altman Z”-Score model remains relevant and effective in detecting potential bankruptcy.